Infrared and UV Imaging Characteristics of Insulator Strings Containing a Zero‐Value Insulator Based on Experiment and Multi‐Physics Simulation. Issue 3 (3rd January 2021) - Wang, Shenghui; Jiang, Tingyue; Li, Wei; Niu, Leilei; Lv, Fangcheng
Abstract : To study the effectiveness of infrared and UV imaging technology to detect zero‐value insulators, the infrared thermal images and UV videos of zero‐value insulators at different positions on insulator strings were collected at different humidities and levels of pollution. The heat and discharge characteristics of the insulator strings were analyzed. The thermal‐electric multi‐physics simulation models were established with COMSOL Multiphysics finite element analysis software. The temperature and electric field distributions of the insulator string under different conditions were verified. The study shows that, under conditions of dry pollution, the insulator strings did not easily discharge, thus the UV imaging method cannot effectively detect a zero‐value insulator. The infrared thermal image shows that the temperature rise in a normal insulator is significantly higher than that in a zero‐value insulator; zero‐value insulators can thus be detected using infrared imaging. In the case of wet pollution, infrared and UV imaging may return erroneous results due to heavy pollution of high conductivity and unevenness of pollution owing to moisture. © 2021 Institute of Electrical Engineers of Japan. Published by Wiley Periodicals LLC.